Baetis pentaphyllus sp. nov., a new species of mayfly (Ephemeroptera: Baetidae) from the Russian Far East - Tiunova, Tatiana M.; Semenchenko, Alexander A. (Zootaxa, 2019)
A new species, Baetis pentaphyllus sp. nov., is described on the basis of larvae from the Far East of Russia (type locality Bolshoi Garmakan River). Larvae of Baetis pentaphyllus sp. nov. may be distinguished from other Baetis species by the presence of only five pairs of tergalii on segments III–VII. The mitochondrial COI sequence obtained from the described species was compared with the data present in GeneBank and BOLD. The DNA barcodes allowed discrimination of B. pentaphyllus sp. nov. from other species of Baetis with available sequence data. The average interspecific K2P distances were 10–15%, which are values well above those associated with intraspecific variation. COI sequences as well as 36 morphological larval characters were analysed using Bayesian inference to relate the described species to the recognized species-groups of the Baetis genus. B. pentaphyllus sp. nov formed a sister clade to B. vardarensis + B. lutheri which belong to the Baetis lutheri species-group.